The performance testing of boars II. Phenotypic and genetic correlations - Ettala, Elsi (Agricultural and Food Science, 1971)
In this study the interrelationships between the various characteristics for the boar material described in the first part were analysed. For this purpose the phenotypic, genetic and intra-sire correlation matrix as well as stepwise multiple regression analyses were calculated by computer for the material of 138 boars. The results showed that there was a very strong correlation between fat thickness and testing score (rG = —0.95***, rP = —0.88***). Of the total variation in the testing score 85.2 % was accounted for by the variation in fat thickness. Although the testing score is made up of the points for fat thickness and growth, the latter accounted for only 9.2 % of the variation in the score. Daily growth was positively associated with the testing score and negatively with the amount of feed units required per growth kilogram, but significantly so only for the intra-sire correlations; the genetic correlations being even, contrary to expectation. The association between growth rate and fat thickness was positive (rG = 0.47***). Of the total variation in feed efficiency the testing score accounted for 35.6 %. A high testing score was associated with a favourable feed efficiency (rg = —0.63***). By correlation studies attempts were also made to find out whether it would be possible to shorten the testing period without decreasing the accuracy. The correlations show that the growth rate can be predicted with an appreciable degree of accuracy already from the weight at the 8th testing week. The correlations between the above weight and growth rates were; rG = 0.84***, rP = 0.82***. From the associations between different characteristics one can decide on the suitability of testing and the consequences of selection for particular traits.